1998
DOI: 10.1002/cbm.245
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in prisons in England and Wales from 1988 to 1995

Abstract: This study is based on an examination of 377 official records (from the English Prison Service's Suicide Awareness Support Unit) of self-inflicted deaths in prisons in England and Wales for the period from 5 February 1988 to 5 November 1995. The study builds on the work of earlier researchers in the area of suicides in prisons (Topp, 1979;Dooley, 1990) and provides a detailed analysis of all selfinflicted deaths occurring in prisons in England and Wales, something never previously undertaken. In this paper we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 10 publications
3
22
0
5
Order By: Relevance
“…The suicide rate of prisoners is substantially higher than for the general population, even after differences in the age structures of the two populations have been accounted for (Towl & Crighton, 1998). A study in Dutch prisons (Kerkhoff & Bernaseo, 1990) reported from an examination of the registration files of 198 attempted suicides that significant risk factors were youth, immigrant origin, being charged with murder or manslaughter, a sentence of a year or longer, using psychotropic medication, and making more frequent visits to the doctor.…”
Section: Introductionmentioning
confidence: 96%
“…The suicide rate of prisoners is substantially higher than for the general population, even after differences in the age structures of the two populations have been accounted for (Towl & Crighton, 1998). A study in Dutch prisons (Kerkhoff & Bernaseo, 1990) reported from an examination of the registration files of 198 attempted suicides that significant risk factors were youth, immigrant origin, being charged with murder or manslaughter, a sentence of a year or longer, using psychotropic medication, and making more frequent visits to the doctor.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, a more detailed analysis of the nature of such difficulties prior to, and during, imprisonment may be used to inform more effective risk management of suicide and ISI in forensic settings. In line with previous research (Towl and Crighton, 1998) one area where further research is crucial is the interaction between prison environments and individual characteristics. This will inevitably require a shift of emphasis away from broad empirical approaches, towards more theoretically grounded analyses.…”
Section: )mentioning
confidence: 55%
“…There is evidence to suggest that prisoners with mental health problems are at greater risk of suicide (Towl & Crighton, 2000), and women are over-represented in those who complete suicide or carry out acts of self harm (Snow, Paton, Oram, & Teers, 2002). In England and Wales, suicides are most prevalent in 'local prisons', where those awaiting trial, those serving short sentences, and those serving the early part of longer sentences are located (Shaw, Baker, Hunt, Moloney, & Appleby, 2004;Towl & Crighton, 1998). By virtue of these functions, local prisons invariably have a high turnover of prisoners, with many people staying for only short periods before they are either released back into the community or transferred to longer-term establishments.…”
Section: The Identification and Management Of Suicide Risk In Local Pmentioning
confidence: 98%